The Role of Iron in Staphylococcus aureus Infection and Human Disease: A Metal Tug of War at the Host—Microbe Interface - van Dijk, Madeleine C.; de Kruijff, Robin M.; Hagedoorn, Peter-Leon (Frontiers in Cell and Developmental Biology, 2022)
Iron deficiency anemia can be treated with oral or intravenous Fe supplementation. Such supplementation has considerable effects on the human microbiome, and on opportunistic pathogenic micro-organisms. Molecular understanding of the control and regulation of Fe availability at the host-microbe interface is crucial to interpreting the side effects of Fe supplementation. Here, we provide a concise overview of the regulation of Fe by the opportunistic pathogen Staphylococcus aureus. Ferric uptake regulator (Fur) plays a central role in controlling Fe uptake, utilization and storage in order to maintain a required value. The micro-organism has a strong preference for heme iron as an Fe source, which is enabled by the Iron-regulated surface determinant (Isd) system. The strategies it employs to overcome Fe restriction imposed by the host include: hijacking host proteins, replacing metal cofactors, and replacing functions by non-metal dependent enzymes. We propose that integrated omics approaches, which include metalloproteomics, are necessary to provide a comprehensive understanding of the metal tug of war at the host-microbe interface down to the molecular level.